Disparidades do Produto Interno Bruto (PIB) per capita no Brasil: Uma análise de convergência em diferentes escalas regionais (1970-2008) - Guilherme Mendes Resende; Jo\~ao Carlos Ramos Magalh\~aes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper investigates the evolution of the Brazilian per capita Gross Domestic Product (GDP) - known as sigma-convergence -, between 1970 and 2008 across four geographic scales (municipalities, micro-regions, meso-regions and states), using four different statistics - coefficient of variation, standard deviation, Theil index and Gini index. The results reveal that the smaller the scale of analysis the smaller the decrease in inequality between 1970 and 2008. The same analysis conducted for two groups (or clubs) shows that the significant reduction in inequality which happened among the states from the North and Northeast disappears as the scale of analysis gets smaller and, according to two of the four statistics, it even increases between the micro-regions and municipalities. As for the rest of the country the results are not strongly affected by the scale reduction. This suggests the occurrence of a distinct convergence process of the per capita GPD between the two groups of regions, characterized by the divergence of the per capita GDP among the micro-regions and municipalities from the North and Northeast and the convergence for the rest of the country. This result shows that there is not one scale that is able to synthesize all the regional dynamics and that is more accurate than the others. In this sense, a multi-scale approach may be useful for a better understanding of the regional per capita GDP disparities in Brazil.
Keywords: O18; O54; R11; 330; regional income disparities; convergence; spatial scales; Brazil